Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Disaster Resilience: A National Imperative (The National Academies Press, 2012)
No person or place is immune from disasters or disaster-related losses. Infectious disease outbreaks, acts of terrorism, social unrest, or financial disasters in addition to natural hazards can all lead to large-scale consequences for the nation and its communities. Communities and the nation thus face difficult fiscal, social, cultural, and environmental choices about the best ways to ensure basic security and quality of life against hazards, deliberate attacks, and disasters. Beyond the unquantifiable costs of injury and loss of life from disasters, statistics for 2011 alone indicate economic damages from natural disasters in the United States exceeded $55 billion, with 14 events costing more than a billion dollars in damages each. One way to reduce the impacts of disasters on the nation and its communities is to invest in enhancing resilience—the ability to prepare and plan for, absorb, recover from and more successfully adapt to adverse events. Disaster Resilience: A National Imperative addresses the broad issue of increasing the nation's resilience to disasters. This book defines "national resilience", describes the state of knowledge about resilience to hazards and disasters, and frames the main issues related to increasing resilience in the United States. It also provide goals, baseline conditions, or performance metrics for national resilience and outlines additional information, data, gaps, and/or obstacles that need to be addressed to increase the nation's resilience to disasters. Additionally, the book's authoring committee makes recommendations about the necessary approaches to elevate national resilience to disasters in the United States. Enhanced resilience allows better anticipation of disasters and better planning to reduce disaster losses-rather than waiting for an event to occur and paying for it afterward. Disaster Resilience confronts the topic of how to increase the nation's resilience to disasters through a vision of the characteristics of a resilient nation in the year 2030. Increasing disaster resilience is an imperative that requires the collective will of the nation and its communities. Although disasters will continue to occur, actions that move the nation from reactive approaches to disasters to a proactive stance where communities actively engage in enhancing resilience will reduce many of the broad societal and economic burdens that disasters can cause.
Keywords: Earth Sciences; Policy for Science and Technology; Conflict and Security Issues

Pathways to Urban Sustainability: A Focus on the Houston Metropolitan Region: Summary of a Workshop - National Research Council (The National Academies Press, 2012)
The workshop was convened to explore the region's approach to urban sustainability, with an emphasis on building the evidence base upon which new policies and programs might be developed. Participants examined how the interaction of various systems (natural and human systems; energy, water, and transportation systems) affected the region's social, economic, and environmental conditions. The objectives of the workshop were as follows:
Keywords: Policy for Science and Technology; Environment and Environmental Studies

Pathways to Urban Sustainability: Research and Development on Urban Systems: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
More than half of the world's people now live in cities. In the United States, the figure is 80 percent. It is worthwhile to consider how this trend of increased urbanization, if inevitable, could be made more sustainable. One fundamental shortcoming of urban research and programs is that they sometimes fail to recognize urban areas as systems. Current institutions and actors are not accustomed to exploring human-environment interactions, particularly at an urban-scale. The fact is that these issues involve complex interactions, many of which are not yet fully understood. Thus a key challenge for the 21st century is this: How can we develop sustainable urban systems that provide healthy, safe and affordable environments for the growing number of Americans living in cities and their surrounding metropolitan areas?
Keywords: Environment and Environmental Studies

Communities in Action: Pathways to Health Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In the United States, some populations suffer from far greater disparities in health than others. Those disparities are caused not only by fundamental differences in health status across segments of the population, but also because of inequities in factors that impact health status, so-called determinants of health.
Keywords: Health and Medicine